Comparison of utility weighted DMFT with patient‐reported oral well‐being. (19th December 2013) - Kay, E. J.; Mills, I.; Tredwin, C.; Lambe, P.; Nassani, M. Z.
Summary This study investigated a method of measuring oral health, as opposed to measuring disease. The objective was to compare DMF score and whole mouth utility scores to a patient‐reported outcome measure (PROM). Disutility values for lost and restored teeth were used to weight the decayed, missing and filled teeths(DMFTs) of 10 adult patients. This gave two whole mouth utility scores (WMU). These scores were then compared with a patient‐reported oral health outcome measure recorded by the use of a visual analogue scale (VAS). The anchors for the VAS were 'my mouth could not be worse' and 'my mouth could not be better'. There was a positive correlation (r = 0·6457) between WMU1 and the patient‐reported outcome measure (P < 0·05) and a negative correlation (r = −0·8383) between WMU1 and DMFT which was significant at the P < 0·01 level. There was a statistically significant positive correlation of r = 0·7926 between WMU2 and the patient‐reported outcome measure (P < 0·01) and a negative correlation (r = −0·9393) between WMU2 and DMFT (P < 0·01). The Pearson's correlation between DMFT and the patient‐reported outcome measure was −0·8757, which was significant at the 0·01 level. Patient reports of their perceived level of health correlate well with DMFT scores. Weighting DMFT scores according to the differential values assigned to missing, or missing and filled, teeth does not increase the degree of correlation between the measure and the patients' personal quantification of their oral health. Decayed, missing and filled teeth therefore seems to adequately capture the patient's sense of well‐being.